Treating hepatitis D with bulevirtide: real-world experience from 114 patients - Dietz-Fricke, Christopher; Tacke, Frank; Zöllner, Caroline; Demir, Münevver; Schmidt, Hartmut H.; Schramm, Christoph; Willuweit, Katharina; Lange, Christian M.; Weber, Sabine; Denk, Gerald; Berg, Christoph P.; Grottenthaler, Julia M.; et al. (JHEP reports, 2023)
Background & Aims - Bulevirtide is a first-in-class entry inhibitor of hepatitis B surface antigen. In July 2020, bulevirtide was conditionally approved for the treatment of hepatitis D, the most severe form of viral hepatitis, which frequently causes end-stage liver disease and hepatocellular carcinoma. Herein, we report the first data from a large multicenter real-world cohort of patients with hepatitis D treated with bulevirtide at a daily dose of 2 mg without additional interferon. - Methods - In a joint effort with 16 hepatological centers, we collected anonymized retrospective data from patients treated with bulevirtide for chronic hepatitis D. - Results - Our analysis is based on data from 114 patients, including 59 (52%) with cirrhosis, receiving a total of 4,289 weeks of bulevirtide treatment. A virologic response defined as an HDV RNA decline of at least 2 log or undetectable HDV RNA was observed in 87/114 (76%) cases with a mean time to virologic response of 23 weeks. In 11 cases, a virologic breakthrough (>1 log-increase in HDV RNA after virologic response) was observed. After 24 weeks of treatment, 19/33 patients (58%) had a virologic response, while three patients (9%) did not achieve a 1 log HDV RNA decline. No patient lost hepatitis B surface antigen. Alanine aminotransferase levels improved even in patients not achieving a virologic response, including five patients who had decompensated cirrhosis at the start of treatment. Treatment was well tolerated and there were no reports of drug-related serious adverse events. - Conclusions - In conclusion, we confirm the safety and efficacy of bulevirtide monotherapy in a large real-world cohort of patients with hepatitis D treated in Germany. Future studies need to explore the long-term benefits and optimal duration of bulevirtide treatment. - Impact and implications - Clinical trials proved the efficacy of bulevirtide for chronic hepatitis D and led to conditional approval by the European Medical Agency. Now it is of great interest to investigate the effects of bulevirtide treatment in a real-world setting. In this work, we included data from 114 patients with chronic hepatitis D who were treated with bulevirtide at 16 German centers. A virologic response was seen in 87/114 cases. After 24 weeks of treatment, only a small proportion of patients did not respond to treatment. At the same time, signs of liver inflammation improved. This observation was independent from changes in hepatitis D viral load. The treatment was generally well tolerated. In the future, it will be of interest to investigate the long-term effects of this new treatment.
Online veröffentlicht: 15. März 2023
Gesehen am 24.08.2023